Overexpression of Siah2 Is Associated With Poor Prognosis in Patients With Epithelial Ovarian Carcinoma. Issue 1 (1st January 2016) - Gao, Ya; Liu, Yunduo; Meng, Fanling; Shang, Pan; Wang, Shuxiang; Zhang, Yu; Sun, Yuqi; Wang, Yuping; Wang, Jing; Chen, Xiuwei
Abstract : Objectives: Seven in absentia homolog 2 (Siah2) is an E3 ubiquitin ligase that is expressed in mammals and is homologous to seven in absentia in Drosophila . Siah2 is involved in the progression of many malignancies. However, the role of Siah2 in ovarian cancer remains unclear. This study aims to evaluate the prognostic value of Siah2 expression for epithelial ovarian carcinoma (EOC) patients. Materials and Methods: Immunohistochemical analysis was conducted using 32 normal ovarian specimens and 122 ovarian carcinoma specimens, respectively. We analyzed the correlations of Siah2 expression with the clinicopathological factors and prognosis of ovarian cancer patients. χ 2 Analysis, Kaplan-Meier method, and multivariate Cox proportional hazard analysis were conducted for statistical analyses. Results: Immunohistochemical staining demonstrated that the expression of Siah2 was higher in the EOC tissues than in the normal tissues. High Siah2 expression positively correlated with histological grade and lymph node metastasis but not with age, histologic type, International Federation of Gynecology and Obstetrics staging, and CA125. Patients with positive Siah2 expression showed lower overall survival and disease-free survival rates than those with negative Siah2 expression ( P < 0.05 for both). Multivariate Cox analysis indicated that Siah2 was an independent parameter for overall survival (hazards ratio, 2.166; 95% confidence interval, 1.182–3.970; P = 0.012) and disease-free survival (hazards ratio, 1.819; 95% confidence interval, 1.030–3.216; P = 0.039). Conclusions: Siah2 is possibly involved in tumor development and progression in EOC. Thus, Siah2 is a promising biomarker for predicting the prognosis of ovarian cancer patients and may serve as a novel target for treating ovarian carcinoma.